Gender-moderated links between urgency, binge drinking, and excessive exercise. Issue 2 (17th February 2016) - Reilly, Erin E.; Dmochowski, Sasha; Schaumberg, Katherine; Earleywine, Mitch; Anderson, Drew
ABSTRACT: Objective : Exercise correlates with alcohol use, but the nature of this relation and the extent to which it is maladaptive remains unclear. Urgency and motives for engaging in drinking and exercise might indicate when these behaviors are problematic. The current study examined whether urgency moderated the association between exercise motivated by weight loss and drinking.Participants : College students ( N = 589, 45.7% male) completed the study during the spring of 2012.Methods : Participants completed self-report assessment measures, including frequency/quantity of alcohol consumption, exercise for weight loss, and urgency, during a single session.Results : Negative urgency moderated the relation between exercise and alcohol consumption in men but not women; the link between excessive exercise and alcohol use was stronger for men with higher levels of urgency.Conclusions : Further clarification of the mechanisms underlying alcohol use and physical activity—particularly maladaptive approaches to exercise—will inform health interventions among college students.